Argumentasi Filosofis-Mistis dalam Pembuktian Tuhan (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2023)
This study aims to present arguments for the existence of God from the perspective of philosophy and Sufism. These arguments simultaneously answer the confusion of the views of modern scientists who believe that all events and incidents in the universe do not need a hypothesis about God. By rational argumentation and witness, God is proven to exist. Vice versa, the conclusion of scientists that God does not exist based on empirical evidence contradicts with the rational law itself. This type of research is qualitative literature, namely the primary sources used as references are literary works such as books and journals. The approach used is rational and critical hermeneutics